If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(8/11)*x-(16/3) = 0
(8/11)*x-16/3 = 0
8/11*x-16/3 = 0 // + 16/3
8/11*x = 16/3 // : 8/11
x = 16/3/8/11
x = 22/3
x = 22/3
| 1/6(9) | | 48/13=3456(65/1345) | | 2z-31=-9z+2y | | (8-2x)(8-2x)-x=0 | | 48/13= | | 328/21= | | 3/2x+1/5=7/5x | | -2/5*-5/2= | | (x-2)=x | | 4(10-11)+8(2-6)= | | 21+r=-1/2 | | 10x-5=-6(x+4)-13 | | (x+3)(x+3)+25=0 | | h=-16t^2+100t+4 | | X^7+2xy+y^6=6x+y | | X^7-6x=0 | | 3(y^2-10)=-13y | | -18x^2-36x+144=0 | | -0.1x+7.17=-0.3x+8.97 | | 2.6=5x+3.4 | | c-2.2+73/5=9.2 | | -49=-7/6w | | b-41/4=21/3-11/4 | | z^3-z^2-z=15 | | 4x^3+48x^2=0 | | y+4=2w-20 | | 5a^2-25a=0 | | Y=20x+16 | | 8x+11y=1100 | | 0.25x-0.1(12000-x)=375 | | senx=2seny | | x/2-3x+3=5x-7 |